Die aandeel van grasse in veldtipes rondom Stellenbosch - Van Rensburg, W. L. J.(Wynand Louw Jansen) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1962.